Hubungan Peran Keluarga Dengan Kemampuan Adl (Activity Daily Living) Pada Lansia Di Wilayah Kerja Puskesmas Perumnas Lubuklinggau Tahun 2025 - Dewi Kartila; Sasteri Yulianti; Murwati Murwati (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Biologically, older adults experience a continuous aging process characterized by a decline in physical resistance to disease. This physical decline can be seen primarily in the ability of older adults to perform activities of daily living such as dressing, defecating or urinating, eating, drinking, walking, sleeping, and bathing. The ability to perform these activities can be used to assess whether older adults are independent or dependent on others. The purpose of this study was to determine the relationship between the role of the family and the ability to perform ADL (activities of daily living) in the elderly in the Lubuklinggau Perumnas Community Health Center Working Area in 2025. The research method used was descriptive research with a cross-sectional approach. The sampling technique used was purposive sampling with a sample size of 33 elderly people in the Lubuklinggau Perumnas Community Health Center Working Area in 2025. The data collection technique in this study used primary data (directly from respondents using questionnaires) and secondary data (data sources available at the Lubuklinggau City Health Office and the Perumnas Lubuklinggau Community Health Center). The data analysis technique in this study used univariate and bivariate analysis. Bivariate analysis used the chi-square test. The results of the univariate analysis showed that most of the respondents (30.3%) had insufficient family support, while a small portion of the respondents (12.1%) had limited ability in activities of daily living.